'Shot While Trying to Escape': Procedural Legality and State-Sanctioned Killing in Nazi Germany. Issue 2 (4th May 2018) - Westermann, Edward B.
ABSTRACT: During the National Socialist dictatorship, SS and police forces made frequent use of the phrase 'shot while trying to escape' to describe the killing of the regime's putative political and racial enemies within the confines of the concentration camps, the Jewish ghettos in the occupied territories, and in anti-partisan operations in the East. In many cases, the phrase normalized the act of murder by providing a veneer of procedural legality that served as both a euphemism and a justification for murder. The practice of summary execution both within National Socialist Germany prior to World War II and the use of such killings after the start of the war illustrates the implementation of one form of legal terror within the Third Reich, and provides an important insight into the ways in which mass murder was rationalized, legitimized, and normalized under the Nazi regime. This practice also demonstrates the manner in which the regime and its murder apparatus employed a fictive legal rational to justify cold-blooded atrocity. Likewise, this study reveals continuity in the use of this practice that extended from the earliest years of the Weimar Republic and into the Third Reich.